2021
DOI: 10.1155/2021/6676149
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Evaluation of Socket Preservation Using Autogenous Tooth Biomaterial and BM-MSC in Dogs

Abstract: This study is aimed at assessing the dimensional alterations occurring in the alveolar bone after premolar extraction in dogs with histomorphometric and histological analysis. After atraumatic premolar extraction, tooth-derived bone graft material was grafted in the extraction socket of the premolar region in the lower jaws of six dogs in two experimental groups. In the second experimental group, BM-MSCs were added together with the graft. The control was left untreated on the opposite side. After twelve weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Articles [26, 27,42] describe various experiments related to the study of the use of an autogenous graft for the preservation of the tooth socket.…”
Section: Use Of An Autogenous Graft For the Preservation Of The Tooth...mentioning
confidence: 99%
See 1 more Smart Citation
“…Articles [26, 27,42] describe various experiments related to the study of the use of an autogenous graft for the preservation of the tooth socket.…”
Section: Use Of An Autogenous Graft For the Preservation Of The Tooth...mentioning
confidence: 99%
“…The article [27] conducted an experiment on dogs. The result of the experiment showed that autogenous material can be used as a material for preserving the tooth socket.…”
Section: обзоры / Reviewsmentioning
confidence: 99%